Elucidating the function of repressor element silencing transcription factor in human breast cancer and its relation with voltage-gated sodium channels-mediated metastasis - Kamarulzaman, Nur Sabrina (2020)
Voltage-gated sodium channels (VGSCs), particularly isoform Nav1.5 and its neonatal splice variant, nNav1.5, is found to be highly upregulated in human breast cancer and its expression/activity associates with strong metastatic potential. Whilst repressor element silencing transcription factor (REST) was discovered as tumour suppressor in various type of carcinomas in which loss/lack of its expression has been linked to aggressive phenotype. The overall aim of this study was to investigate the role of REST in regulating Nav1.5 and nNav1.5 expression in human breast cancer cells. Real-time PCR and Western blotting were conducted to compare the mRNA and protein expression levels of target molecules (Nav1.5, nNav1.5, REST, HDAC1, HDAC2, HDAC3, MMP2, N-cadherin), respectively, between the non-cancerous breast epithelial cell line (MCF-10A), the less aggressive human breast cancer cell line (MCF-7) and the highly aggressive human breast cancer cell line (MDA-MB-231). The possible REST binding sites on Nav1.5 promoter sequence was predicted using online software JASPAR2018. Since MCF-7 cells has been reported to expressed higher REST expression, siRNA-mediated REST knockdown and treatment using histone deacetylase (HDAC) inhibitor, trichostatin A (TSA) was performed only on MCF-7 cells. Cell growth and metastatic behaviours of the cells were also assessed by functional assays (MTT, lateral motility and migration assays). REST mRNA was detected in all three cell lines with the highest expression in MCF-7 cells (p<0.05). Similarly, REST protein expression was also detected in all three cell lines, with the highest expression in MCF-7 cells (p<0.05). The mRNA expression of Nav1.5 (p<0.01) and nNav1.5 (p<0.05) was higher in MDA-MB-231 cells compared to MCF-7 cells and not detected in MCF- 10A cells. Correspondingly, Nav1.5 protein expression was also higher in MDAMB- 231 cells compared to MCF-7 cells (p<0.05). Twelve REST binding sites in Nav1.5 promoter were predicted by JASPAR2018. Although mRNA and protein expression of REST were successfully knockdowned (p<0.05), however, no significant change was observed on Nav1.5 and nNav1.5 mRNA level. Additionally, although only HDAC2 mRNA expression was significantly higher in MCF-7 cells compared to MDA-MB-231 cells (p<0.05) (from the basal comparison analysis), instead, in the MCF-7-REST knockdown cells, HDAC1 mRNA expression was significantly reduced (p<0.05). In the TSA treated MCF-7 cells, HDAC2 mRNA level was significantly reduced (at 1000 and 10 000 ng/ml, p<0.001), similarly, REST mRNA expression was significantly reduced (at 100 (p<0.05), 1000 (p<0.001) and 10 000 (p<0.0001) ng/ml)). Interestingly, TSA significantly enhanced mRNA expression of Nav1.5 (at 1000 (p<0.05) and 10 000 (p<0.01) ng/ml) and nNav1.5 (at 10 000 ng/ml, p<0.01). This was followed by enhanced cell migration (at 1000 and 10 000 ng/ml, p<0.05), which was confirmed by significant upregulation of two metastasis-related genes, MMP2 (p<0.01) and N-cadherin (p<0.05). In conclusion, REST regulates Nav1.5/nNav1.5 expression via inhibition by HDAC2 in the less aggressive breast cancer cells (which did not occur in aggressive breast cancer due to lack of REST), providing a revelation that Nav1.5/nNav1.5 expression in breast cancer could be regulated by epigenetics.